Estudo de resistência à fadiga de uniões parafusadas submetidas à carga axial cíclica em função do comprimento do parafuso - Thompson, Felipe de Freitas (2017)
In this study, endurance tests were conducted in bolted joints to plot S-N curves. The bolts tested were the M8, class 8.8 of three different lengths, 45, 60 and 80 mm. A device was machined to support cyclic axial load to carry on the endurance tests. Tensile tests were conducted on the bolts in order to establish its mechanical properties. For the performance of the endurance tests, it was applied a preloading equal to 90% of the yield strength. Hence, the stiffness was calculated according to different existing theories. Also, it was calculated the alternate stress and stress amplitude on the bolt. The obtained endurance limits results, as well as the calculated stiffness, alternate stress and stress amplitude were compared with results achieved in similar studies. Moreover, it were developed axysimmetric computational models of the 45 and 80 mm bolted joints, with the aim of verifying the stress level carried by the bolt when it is submitted to the pre load. The results showed a maximum stress 10% higher on the 45 mm bolted joint.